Unter Beobachtung | Under Surveillance Vertriebenenverbände im Blick der sozialistischen Sicherheitsdienste | The Monitoring of Expellee Organizations by the Socialist Security Services - Lehr, Stefan (Journal für Kultur und Geschichte der Deutschen im östlichen Europa (JKGE) / Journal for Culture and History of the Germans in Eastern Europe, 2022)
This volume is the first to examine how this "enemy" was observed and perceived by the intelligence services by looking at various case studies from the GDR, Poland, Czechoslovakia, Hungary, Romania, and Yugoslavia.